Development of graphene-enhanced ester-based drilling fluid - Razali, Siti Zulaika (2019)
Synthetic base fluids have been introduced to substitute non-environmentally friendly diesel at strict discharged regulation area, particularly in sensitive marine zone. Issues such as high viscosity and pour point, poor thermal and hydrolytic stabilities limit the manipulation of ester for various drilling fluid’s density and oil- water ratio (OWR) at high pressure-high temperature (HPHT) although it is superior in biodegradability, lubricity and zero aromatic content. In addition to that, nanomaterials have been proven in improving drilling fluid’s properties, especially in water based. Nevertheless, there is very limited knowledge of nanomaterial’s role in the improvement of ester-based drilling fluid (EBDF).